Consumer Perception And Awareness Towards Online Shoppingin Nagapttinam District - Dr. C. Subramanian , M. Jayalakshmi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Online shopping is the use of electronic means to carryout buying over the internet at any given time. An online shop is where purchasing of goods and services is done directly with consumers/client is known as Business to Consumer (B2C) online shopping. On the other hand, the Business to Business (B2B) online shopping takes place when a business buys from another business. Before now, while emphasis of a business turnover was about durable good on the internet, today nearly every product or even service can be bought and sold via the internet. The internet, which is seen as a new marketing channel presents a different and unique shopping environment for consumers, provides a different shopping platform by which customers can shop without having to visit the stores which can be very exhausting.